2013
DOI: 10.3996/032013-jfwm-025
|View full text |Cite
|
Sign up to set email alerts
|

Can Reliable Sage-Grouse Lek Counts Be Obtained Using Aerial Infrared Technology?

Abstract: More effective methods for counting greater sage-grouse (Centrocercus urophasianus) are needed to better assess population trends through enumeration or location of new leks. We describe an aerial infrared technique for conducting sage-grouse lek counts and compare this method with conventional ground-based lek count methods. During the breeding period in 2010 and 2011, we surveyed leks from fixed-winged aircraft using cryogenically cooled mid-wave infrared cameras and surveyed the same leks on the same day fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 27 publications
1
21
0
Order By: Relevance
“…have been detected (Gillette et al. , , McCafferty ). The automated‐detection method used by Christiansen et al.…”
Section: Overview Of Image‐analysis Techniquesmentioning
confidence: 99%
“…have been detected (Gillette et al. , , McCafferty ). The automated‐detection method used by Christiansen et al.…”
Section: Overview Of Image‐analysis Techniquesmentioning
confidence: 99%
“…previous aerial infrared studies of lekking grouse that also reported correlations between infrared cameras and ground counts (Gillette et al 2013(Gillette et al , 2015. However, we extend this study to provide robust estimates based on actual proportion of grouse counted from the aircraft relative to a 'true' number on the ground.…”
Section: Sitementioning
confidence: 70%
“…Furthermore, AIRIS can also be used to assess the accuracy of GBV counts, as we demonstrate in this study. Although past studies have compared similarities between counts recorded with infrared cameras to those collected on the ground for sharptailed grouse Tympanuchus phasianellus and sage-grouse (Gillette et al 2013(Gillette et al , 2015, sightability of newer AIRIS has not been formally estimated.…”
mentioning
confidence: 99%
“…Prevailing conditions, primarily changes in snow coverage and potential snow burrowing by sage-grouse at night, led to some deviations in standard flight protocols (J. P. Romero, personal communication), which precluded us from adding a detection component to our study design. The infrared flights produced similar counts of sage-grouse during spring lek surveys compared to ground-based observers (Gillette et al 2013); however, spring lek surveys occurred at known sage-grouse leks, allowing the pilot to home in on a specific location where grouse were likely to occur. Although not incorporating detection likely added some bias to our analyses, we standardized the data within our analyses as best as possible by including only daytime detections during conditions verified to work during our study.…”
Section: Discussionmentioning
confidence: 86%
“…We assumed that detection was similar across survey transects. We feel this was a reasonable assumption during the day given the ability of infrared to accurately count prairie grouse at leks (Gillette et al , ). There is a paucity of information on the makeup of winter sage‐grouse flocks, but available information suggests that individuals in winter flocks are often located within 200 m of each other (Beck ).…”
Section: Methodsmentioning
confidence: 97%